(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The use of modern unmanned aviation technologies when conducting search and rescue operations, respectively when overcoming the consequences of disasters is an economically justified approach to increase the effectiveness of operations, reducing the costs of their implementation. The nature of the operations implies working in an environment of high uncertainty with variety of stakeholders, which requires the implementation of additional measures to achieve the target levels of aviation safety. To tackle the risks associated with any Unmanned Aerial Systems (UAS) operations JARUS (Joint Authorities for Rulemaking in Unmanned Systems) has proposed a document called SORA (Specific Operations Risk Assessment) adopted as acceptable means of compliance by many civil aviation authorities. Admittedly, SORA was developed with civil use of UAS in mind. However, considering its comprehensiveness in risk assessment it is a good starting point to evaluate its applicability at disaster relief operations and adaptability to state aircraft operations. As a rule, activities to overcome the consequences of disasters are the responsibility of the state, therefore it is normal to expect that the capabilities to use UAS will be created and predetermines the relevance of the presented topic. In the current article the team analyses SORA applicability from the perspective of emergency services as state aircraft operations. Thus, the purpose of this article is to explore the possibilities and to justify the need of implementing a timely procedure and to show an example risk analysis performed for this type of operations, when operating with state unmanned aircraft. Of course, some of the conclusions drawn here for emergency services can be easily transposed to other state UAS operations.